2019
DOI: 10.1101/688234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classifying disease-associated variants using measures of protein activity and stability

Abstract: Decreased cost of human exome and genome sequencing provides new opportunities for diagnosing genetic disorders, but we need better and more robust methods for interpreting sequencing results including determining whether and by which mechanism a specific missense variants may be pathogenic. Using the protein PTEN (phosphatase and tensin homolog) as an example, we show how recent developments in both experiments and computational modelling can be used to determine whether a missense variant is likely to be pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…Our observation that single amino acid changes in MLH1 are sufficient to cause degradation is similar to results from multiple other proteins including recent deep mutational scans on PTEN and TPMT (Matreyek et al, 2018), our previous results on MSH2 in human cells (Nielsen et al, 2017), and earlier observations on Lynch syndrome MSH2 variants in yeast (Gammie et al, 2007; Arlow et al, 2013). Our structural stability calculations predict that a relatively mild destabilization of just a few (~3) kcal/mol is sufficient to trigger MLH1 degradation, an observation in line with previous studies on other proteins (Bullock et al, 2000; Nielsen et al, 2017; DDD Study et al, 2017; Scheller et al, 2019; Jepsen et al, 2019; Caswell et al, 2019). Although the absolute thermodynamic stability of MLH1 is unknown, both in vitro and in a cellular context, it is possible that the 3 kcal/mol destabilization necessary to trigger degradation is lower than that required to reach the fully unfolded state.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our observation that single amino acid changes in MLH1 are sufficient to cause degradation is similar to results from multiple other proteins including recent deep mutational scans on PTEN and TPMT (Matreyek et al, 2018), our previous results on MSH2 in human cells (Nielsen et al, 2017), and earlier observations on Lynch syndrome MSH2 variants in yeast (Gammie et al, 2007; Arlow et al, 2013). Our structural stability calculations predict that a relatively mild destabilization of just a few (~3) kcal/mol is sufficient to trigger MLH1 degradation, an observation in line with previous studies on other proteins (Bullock et al, 2000; Nielsen et al, 2017; DDD Study et al, 2017; Scheller et al, 2019; Jepsen et al, 2019; Caswell et al, 2019). Although the absolute thermodynamic stability of MLH1 is unknown, both in vitro and in a cellular context, it is possible that the 3 kcal/mol destabilization necessary to trigger degradation is lower than that required to reach the fully unfolded state.…”
Section: Discussionsupporting
confidence: 89%
“…While those have slightly higher overall accuracy, they do not directly indicate the underlying molecular reason for pathogenicity. Incidentally, we note that by analyzing both calculations and multiplexed assays of variant effects, we recently found that ~60% of disease-causing variants in the protein PTEN were caused by destabilization and a resulting drop in cellular abundance (Jepsen et al, 2019). On the other hand, while stability prediction is very useful for accurate identification of many pathogenic variants, it may have lower overall sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Pinpointing which variants are in the detrimental group, and the biochemical and biophysical mechanisms underlying loss of fitness, is important for example for assessing pathogenicity of so-called variants of uncertain significance (Richards et al, 2015) and understanding the mechanistic origins of disease. methods are important to predict and understand variant effects, and in some cases they may be even be more accurate than MAVEs for this purpose (Jepsen et al, 2020;Frazer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In such tests, it has been shown that various sequence-based approaches, including deep-learning methods, can achieve very high accuracy (Riesselman et al, 2018;Livesey and Marsh, 2020). Indeed, we and others have successfully applied sequence analysis and biophysical stability calculations for identification and analysis of pathogenic variants, although these methods were not trained on clinical variants (Pey et al, 2007;Yin et al, 2017;Nielsen et al, 2017;Gray et al, 2018;Scheller et al, 2019;Cline et al, 2019;Abildgaard et al, 2019;Jepsen et al, 2020;Frazer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation